2015
DOI: 10.2136/vzj2014.09.0125
|View full text |Cite
|
Sign up to set email alerts
|

Organic Growing Media: Constituents and Properties

Abstract: Organic growing media are essentially bulk products. Availability in large quantity allied to its excellent air and water retention, low pH and salinity, and freedom from pests and diseases has led to peat being the dominant organic constituent of growing media in many parts of the world for the last 50 yr. The unique microporous properties of Sphagnum peat and its resistance to degradation are matched by few other growing media constituents. Nevertheless, local scarcity of Sphagnum peat and the expense of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 74 publications
1
77
0
7
Order By: Relevance
“…Therefore, according to Massa et al [87], efforts should involve the adaptation of new technologies for tracking raw materials and supporting sustainable circular chains for compost production at a local level. In addition, strict quality control procedures are essential in preparing composts for use in growing media [22].…”
Section: Feedstock Waste Use As Growing Medium For Plant Production Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, according to Massa et al [87], efforts should involve the adaptation of new technologies for tracking raw materials and supporting sustainable circular chains for compost production at a local level. In addition, strict quality control procedures are essential in preparing composts for use in growing media [22].…”
Section: Feedstock Waste Use As Growing Medium For Plant Production Rmentioning
confidence: 99%
“…The extensive use of peat as a basic and main component of substrates is due to relatively low costs in these areas, its excellent chemical, biological, and physical properties with low nutrient content, low pH, a unique combination of high water-holding capacity by high air space and drainage characteristics, light weight, and freedom from pests and diseases [14,16,21]. The unique microporous properties of Sphagnum peat and its resistance to degradation are matched by few other growing medium constituents [22].…”
Section: Introductionmentioning
confidence: 99%
“…Such substrates typically have an inorganic and organic component (Bilderback et al, 2005). The organic component provides high porosity, low bulk density, and nutrient retention (e.g., water, nutrient ions) (Raviv et al, 1986), which makes Sphagnum peat moss a strongly suitable option with widespread use (Carlile et al, 2015;Robinson and Lamb, 1975). However, increasing expense and competing uses for peat (Caron et al, 2015), impacts of its harvest on wetland ecosystems (Barkham, 1993;Robertson, 1993), including loss of peat bogs as a key global C sink (Cleary et al, 2005), and its perception as unsustainable (Caron et al, 2015) have spurred recent investigations of substitutes for peat in soil-free substrates, including biomass waste products such as compost and sawdust (e.g., Ceglie et al, 2015;Maas and Adamson, 1972;Wright et al, 2009;Álvarez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An important issue for the growing media industry is worldwide, economic, and environmental pressures to replace some constituents used in growing media mixes. In Carlile et al (2015), principal organic constituents of media and their properties are reviewed with particular attention to finding alternatives to peat, given concerns about environmental sustainability. The authors found that recent advances in the processing and quality control of coconut coir—a rapidly renewable product—make it a good alternative to peat.…”
Section: Sources Of Organic Materialsmentioning
confidence: 99%